1995
DOI: 10.3109/07357909509024927
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tumor Cell Growth by Anthocyanins In Vitro

Abstract: Bioflavonoids, extracted from flower petals, were examined for their growth inhibitory effect on cells in culture. They were found to significantly suppress the growth of the cultured cells. Anthocyanins tended to show greater inhibitory effect than other flavonoids. Commercially synthesized or purified aglycones of flavonoids were also studied for their suppression of tumor cells. The anthocyanins were more effective than other flavonoid aglycones, although the aglycones were easily inactivated under the cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(168 citation statements)
references
References 5 publications
7
144
0
8
Order By: Relevance
“…Beras hitam memiliki kandungan antosianin tinggi yang terletak pada lapisan perikarp, yang memberikan warna ungu gelap (Ryu et al, 1998;Takashi et al, 2001). Antosianin telah diakui sebagai bahan pangan fungsional kesehatan karena aktivitas antioksidan (Nam et al, 2006;Philpott et al, 2004;Satue-Gracia et al, 1997), antikanker (Hyun dan Chung, 2004;Kamei et al, 1995), hipoglikemia (Tsuda et al, 2003), dan efek anti inflamasi (Tsuda et al, 2002). Fungsi-fungsi tersebut memberikan efek sinergis dengan berbagai nutrisi secara in vivo.…”
Section: Pendahuluanunclassified
“…Beras hitam memiliki kandungan antosianin tinggi yang terletak pada lapisan perikarp, yang memberikan warna ungu gelap (Ryu et al, 1998;Takashi et al, 2001). Antosianin telah diakui sebagai bahan pangan fungsional kesehatan karena aktivitas antioksidan (Nam et al, 2006;Philpott et al, 2004;Satue-Gracia et al, 1997), antikanker (Hyun dan Chung, 2004;Kamei et al, 1995), hipoglikemia (Tsuda et al, 2003), dan efek anti inflamasi (Tsuda et al, 2002). Fungsi-fungsi tersebut memberikan efek sinergis dengan berbagai nutrisi secara in vivo.…”
Section: Pendahuluanunclassified
“…They have been recognized as health-promoting functional food ingredients due to their antioxidant activity (Nam et al 2006;Philpott et al 2006;Satue-Gracia et al 1997), which has been reported to reduce the risk of coronary heart disease (Stocker and O'Halloran 2004;Waterhouse 1995). Anthocyanins are also known to have anti-cancer (Hyun and Chung 2004;Kamei et al 1995;Zhao et al 2004), hypoglycemic (Tsuda et al 2003), and anti-inflammatory effects (Tsuda et al 2002) and have been used in the treatment of various circulatory disorders (Bettini et al 1985). Furthermore, these functions provide synergic effects with various nutrients in vivo, so their nutritional values are of great interest recently.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Generally, potato has not been regarded as a food rich in antioxidants, but several researchers have found that depending on the genetic variety, some potato contain considerable amounts of polyphenols, flavonoids, and anthocyanins. 3,4) Furthermore, recently new varieties of potato have been developed around the world to find new uses, as these are rich in antioxidants.…”
mentioning
confidence: 99%